Handling for plant parameters variation of control system - Chong, Kok Leong (2015)
Each year, the demand of increase the areal density of HDD grows in a range of 10% [1]. Developing robust and reliable control algorithm for HDDs is an ongoing task in the HDD industry. By evaluating the model of a HDD actuator servo system, the author has a better understanding on how the actual system looks like. This project is concerned on the study of the plant parameters variation of control system. This dissertation is concerned on the design of a PID controller to handle the robustness issues, such as disturbance rejection and resonance compensation of a Hard Disk Drive (HDD) actuator servo system. The design of a simple PID controller and notch filter will be based on the basic control theory studied in the course EE3011 (Modelling and Control) and EE4265 (Process Control System). Those designs mentioned will be done using Matlab and SIMULINK. Furthermore, an attempt has been made to output an optimal controller using Graphical User Interface (GUI) in Matlab.